2015
DOI: 10.3892/mco.2015.654
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and toxicity of radiotherapy for refractory bone and soft tissue sarcomas

Abstract: Abstract. Surgical resection is a well-established treatment option for sarcoma. However, anatomical barriers often hamper radical surgical procedures. The treatment of unresectable sarcoma, including local or distant failures following initial treatment, is challenging. The aim of the present study was to analyze the outcome of radiotherapy (RT) for refractory sarcoma, including unresectable, metastatic and recurrent disease, following radical treatment. We retrospectively reviewed a total of 67 tumors in 28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“… 11 Yet, throughout the past years, several studies investigating novel treatment options have been published, with sometimes promising results ( Table 1 ). Besides conventional RTX as the standard of care for local treatment of some histological subtypes such as Ewing’s sarcoma, 12 particle therapy with protons or heavy ions may be used in unresectable or incompletely resected bone sarcoma – including relatively radio-resistant tumours as osteosarcoma – achieving adequate LC rates, especially in small tumours and single-site disease. 13 , 14 Furthermore, chemo-embolization with N-2-btyl-cyanoacrylate (NBCA) has been shown to be effective for symptom palliation in unresectable or recurrent bone sarcomas of the shoulder girdle or pelvis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 11 Yet, throughout the past years, several studies investigating novel treatment options have been published, with sometimes promising results ( Table 1 ). Besides conventional RTX as the standard of care for local treatment of some histological subtypes such as Ewing’s sarcoma, 12 particle therapy with protons or heavy ions may be used in unresectable or incompletely resected bone sarcoma – including relatively radio-resistant tumours as osteosarcoma – achieving adequate LC rates, especially in small tumours and single-site disease. 13 , 14 Furthermore, chemo-embolization with N-2-btyl-cyanoacrylate (NBCA) has been shown to be effective for symptom palliation in unresectable or recurrent bone sarcomas of the shoulder girdle or pelvis.…”
Section: Resultsmentioning
confidence: 99%
“… 13 , 14 , 66 Definite RTX in patients with unresectable non-rhabdomyosarcoma STS was shown to result in median disease-free survival rates of 12 months (range 0.1 years to 9.4 years). 12 , 65 Likewise, particle therapy seems to be effective in unresectable STS, although studies identified in the current systematic review either reported on few STS cases only 13 , 14 , or collectively analysed pelvic STS with retroperitoneal, chest wall- and abdominal wall-STS. 65 Of note, carbon ion radiotherapy seems to be more effective regarding LC in liposarcoma and undifferentiated pleomorphic sarcoma (UPS) as compared with malignant peripheral nerve sheath tumour or synovial sarcoma.…”
Section: Soft Tissue Sarcomasmentioning
confidence: 92%
See 1 more Smart Citation
“…Overall, although our patient cohort tolerated RT relatively well, requiring little or no medical intervention for treatment complications, the morbidity of RT in this study and others was not insignificant. 7,20,26 With the advances in RT techniques 20 and the incorporation of charged-particle therapy, 8,27 it is hoped that continued progress in enhancing the therapeutic ratio through the reduction in treatment morbidity will improve outcomes for those patients with osteosarcoma who may benefit from RT.…”
Section: Discussionmentioning
confidence: 99%
“…The linear-quadratic (LQ) model has been widely used to compare differentially fractionated radiotherapeutic regimens, despite several limitations (35). Our previous studies have described a prescription using IMRT based on the LQ model (23,36,37). Hypofractionated radiotherapy at higher doses per fraction may increase radiation-induced damages due to direct cytotoxicity, and may lead to microvascular disruption (38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%